Peran Regulator Dalam Mendorong XBRL Pada Pelaporan Keuangan di Pasar Modal Indonesia: Studi Kualitatif Pada Bursa Efek Indonesia - Andriyawan E. Karim; Fitri Nurhayati M; Hartai Tuli; Mattoasi Mattoasi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the strategic role of the regulator, namely the Indonesia Stock Exchange (IDX), in promoting the adoption of eXtensible Business Reporting Language (XBRL) in the financial reporting of listed companies in the Indonesian capital market. The adoption of XBRL represents a response to the limitations of traditional reporting formats, which are generally presented in unstructured document forms (PDF), thereby hindering the efficiency of data analysis and comparability. Using a qualitative approach with a case study of the IDX, this study illustrates how the regulator’s role.